FACTORS INFLUENCING TOWARDS THE PRUCHASE INTENTIONS OF READY-TO-EAT FOOD PRODUCTS AMONG THE CONSUMERS IN CHENNAI CITY - Babu, R.Suresh; Balaji, V.; Gajenderan, Vijayakumar (International Journal of Research -GRANTHAALAYAH, 2021)
Aim: The study’s purpose is to find out the factors influencing towards the Purchase of Ready-to-Eat food products among the consumers in Chennai city. Data Sources: The study used both primary and secondary data. The secondary data obtained from the articles, research papers, newspapers, and magazines. The primary data is collected from the consumers of Ready-to-Eat food products in Chennai city. The preliminary data sourced from the consumers through structured questionnaires. Sample size & Method: The study employed the convenience sampling method. Overall, 400 questionnaires were distributed, out of which 392 filled questionnaires were collected from the consumers. Out of 392 questionnaires, seven questionnaires rejected due to inadequate information provided by the consumers. Finally, 385 questionnaires were used for the final analysis. Findings: The study found that the factors namely Convenience, Quality, Mood, Sensory Appeal, Price, and Stress-free significantly influencing the purchase intentions of Ready-to-Eat food products among the consumers in Chennai city.